Thymoquinone content in marketed black seed oil in Malaysia - Alkhatib, Hamzeh; Mawazi, SaeidMezail; Al-Mahmood, SinanMohammed Abdullah; Zaiter, Ahmad; Doolaanea, Abd Almonem (Wolters Kluwer, 2020)
Thymoquinone (TQ) is the major active compound in black seed oil (BSO). Many pharmacological effects of TQ, such as anti-inflammatory, hypoglycemic, antioxidant, immune stimulator, and anticancer, have been reported. TQ can be considered as a biomarker for BSO, but its content in the commercial products is rarely reported. TQ content varies based on the oil source and extraction method. This study aimed to quantify the TQ content in the commercial BSO products in Malaysia and to evaluate whether the products can be used as a source of TQ for therapeutic benefits. TQ was quantified using an established high-performance liquid chromatography (HPLC) method. TQ human equivalent dose (HED) was calculated based on reported animal studies from literature, and theoretical BSO amount containing the TQ dose was calculated based on the HPLC analysis. TQ content in the commercial BSO products ranged from 0.07% wt/wt to 1.88% wt/wt. The product with the highest TQ concentration is approximately 27-fold higher than the product with the lowest TQ concentration. Consequently, theoretical BSO amounts needed for specific diseases varied and some products cannot provide practical amount of TQ. This study recommends the regulation of TQ content in BSO and suggests that the BSO might be fortified with extra TQ to be effectively used in some diseases.